Genetic and Environmental Influences on Cortisol Regulation Across Days and Contexts in Middle-Aged Men - Franz, Carol E. (Springer US, 2010)
Cortisol is an indicator of hypothalamic–pituitary–adrenal axis responsivity to stress, but few twin studies have examined the heritability of cortisol concentrations in adults across the diurnal cycle and in different contexts. Saliva samples were provided by 783 middle-aged male twins on one laboratory and two home days as part of the Vietnam Era Twin Study of Aging. Significant cortisol heritability estimates were found for laboratory measures only: awakening (.56); 30 min after awakening (.48); 1000 h (.42); mean output across the day (.43); and mean cortisol awakening response (.64). Twin correlations at home were low. In the laboratory, they were unchanged for fraternal twins, but increased for identical twins. Greater measurement error at home did not appear to account for home-laboratory differences. The results suggest that genetic factors influence cortisol responses to specific environmental stressors. Thus, cortisol levels are correlated in identical twins only when they undergo similar experiences.